Development of Sensor using Surface Electronic Conduction of Natural Rubber - Ghosh, P.K.; Sarkar, A. (Asian Journal of Chemistry, 2011)
Development of gas sensors using non toxic natural materials has become a new trend of present day sensor research. In present paper application potential of natural rubber in gas sensing has been studied by exploiting the property of surface electronic conduction, worth of natural rubber as NH3 gas sensor and also its sensitivity to humidity and CO2. Thus the typical gas sensing phenomenon in rubber surface claims importance in both theoretical and experimental research.